Enhancing Independent Participation Within Vocational Activities for an Adolescent With ASD Using AAC Video Visual Scene Displays. Issue 2 (June 2019) - Babb, Salena; Gormley, Jessica; McNaughton, David; Light, Janice
Adolescents with autism spectrum disorder (ASD) often require support both for learning new skills and for communication. This study used a multiple baseline across activities design to evaluate the effect of videos with integrated visual scene displays (video VSDs), presented using a tablet-based app, on the percentage of steps completed independently within vocational training tasks by an adolescent with ASD and complex communication needs (CCN). Using the video VSDs, the participant met the mastery criterion for completing three tasks (including participation in communication exchanges) in a vocational setting. The results provide evidence that video VSDs may provide an effective support both for learning new skills in vocational contexts, and as a method of augmentative and alternative communication for individuals with ASD and CCN.